The Level 3 Based SPICE Model for Low-Voltage Pentacene Thin Film Transistors - Akkan, Nihat; Sedef, Herman; Altun, Mustafa (IEEE, 2022)
A modeling technique is presented for organic thin film transistors (OTFTs) in LTspice platform, using the Level 3 MOSFET model with additional four model parameters. First, the mobility model equation is simplified. Next, the evaluated drain current of the Level 3 model is manipulated proportionally to the recently proposed OTFT mobility model. On the other hand, the model performance is enhanced in the subthreshold regime adding off-state current. This behavioral model is built by using one PMOS transistor and two behavioral current sources. Then, the Level 3 model parameters are obtained fitting the model equations to the low-voltage pentacene-based OTFT data using previously studied metaheuristics-based parameter extraction approach. Finally, the behavioral model based on the Level 3 is simulated in LTspice while the gate and drain voltages are both ranging from 0 to -3 V. It is validated within this range, comparing the experimental and modeled characteristic curves. This model can be more convenient for very large OTFT-based digital circuit simulations.
Keywords: Organic Thin Film Transistors; Level-3; SPICE; Behavioral modeling; Pentacene; PARAMETER EXTRACTION; COMPACT MODEL; Computer Science; Engineering; Mathematics